Advances in Combustion of Gases, Liquid Fuels, Coal and Biomass - Sunderland, Peter B. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue of Energies on "Advances in Combustion of Gases, Liquid Fuels, Coal and Biomass" includes five manuscripts on combustion research related to energy production. Both fundamental and applied research is included. The papers contain state-of-the-art experiments, computations, and theory. Combustion provides an estimated 85% of the world's energy consumption. Advances in combustion research can benefit society in three main ways. Improving energy efficiency can reduce fuel consumption. Improving emissions can reduce climate change and adverse health effects. Improving fire and explosion safety can protect people, property, and the environment. The topical areas covered by this Special Issue are broad. It is hoped that this breadth will lead to a better understanding of combustion and improved diagnostic and numerical tools. This, in turn, may result in improved combustors, a cleaner environment, novel fuels, and improved safety and energy security.